Design of intelligent multifinger gripper for a robotic arm using a DSP-based fuzzy controller - Salami, Momoh Jimoh Emiyoka; Mir-Nassiri, Nazim; Sidek, Shahrul Na'im (2000)
The design and modeling of a robotic arm gripper that has elements of intelligent decision making while grasping object has been recently discussed. This new system is different in using an appropriate controlling scheme so that the correct force is applied to pick an object without dropping or crushing it. This is achieved by controlling the shear stresses at the interface material between finger-ends and the object using smart sensors and intelligent controller. A new slip sensor that is based on the operation of optical encoder is used to monitor the slip rate as a result of insufficient force being applied to pick an object. A two-stage control scheme is suggested for the implementation of this system. First a limit switch is used to control the positioning of the fingers thereby solving the problem of uncertainty in the location and orientation of the object. Then, to ensure that an appropriate force is used in picking up an object a fuzzy logic controller is used. The use of TMS320C24XX series DSP controller to implement the control strategy provides the flexibility needed in altering the control code and the prototype can be tested at low cost.